High-density lipoprotein's vascular protective functions in metabolic and cardiovascular disease – could extracellular vesicles be at play?. Issue 22 (27th November 2020) - Beazer, Jack D.; Patanapirunhakit, Patamat; Gill, Jason M.R.; Graham, Delyth; Karlsson, Helen; Ljunggren, Stefan; Mulder, Monique T.; Freeman, Dilys J.
Abstract: High-density lipoprotein (HDL) is a circulating complex of lipids and proteins known primarily for its role in reverse cholesterol transport and consequent protection from atheroma. In spite of this, therapies aimed at increasing HDL concentration do not reduce the risk of cardiovascular disease (CVD), and as such focus has shifted towards other HDL functions protective of vascular health – including vasodilatory, anti-inflammatory, antioxidant and anti-thrombotic actions. It has been demonstrated that in disease states such as CVD and conditions of insulin resistance such as Type 2 diabetes mellitus (T2DM), HDL function is impaired owing to changes in the abundance and function of HDL-associated lipids and proteins, resulting in reduced vascular protection. However, the gold standard density ultracentrifugation technique used in the isolation of HDL also co-isolates extracellular vesicles (EVs). EVs are ubiquitous cell-derived particles with lipid bilayers that carry a number of lipids, proteins and DNA/RNA/miRNAs involved in cell-to-cell communication. EVs transfer their bioactive load through interaction with cell surface receptors, membrane fusion and endocytic pathways, and have been implicated in both cardiovascular and metabolic diseases – both as protective and pathogenic mediators. Given that studies using density ultracentrifugation to isolate HDL also co-isolate EVs, biological effects attributed to HDL may be confounded by EVs. We hypothesise that some of HDL's vascular protective functions in cardiovascular and metabolic disease may be mediated by EVs. Elucidating the contribution of EVs to HDL functions will provide better understanding of vascular protection and function in conditions of insulin resistance and potentially provide novel therapeutic targets for such diseases.